Pengaruh Gaya Kepemimpinan, Kepuasan Kerja dan Motivasi Terhadap Kinerja Karyawan Top Yummy di Jakarta - Rayen Eduard Wijaya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this study was to determine the effect of leadership, job satisfaction, motivation, on employee performance. The sample selection technique used in this study is a non-probabilty sampling method, namely purposive sampling. The population of this research is the Jakarta branch of Top Yummy employees. The research sample was taken from 100 respondents who had worked at least 6 months at the Top Yummy Jakarta branch. Data analysis using SmartPLS 3.0. Data collection is done by distributing questionnaires. The results are: (a) leadership has a positive and significant influence on employee performance in the Jakarta branch of Top Yummy, (b) job satisfaction has a positive and significant influence on the employee performance of the Jakarta branch of Top Yummy. (c) Motivation has a positive and significant influence on employee performance at the Jakarta branch of Top Yummy